ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTASI DALAM NEGERI DI JAWA TENGAH TAHUN 1980-2002 - Setyowati, Eni; Fatimah NH, Siti (Universitas Muhammdaiyah Surakarta, 2007)
Investment is one of important component for sustainable economic development process. The research objective that want achieved is to estimate influence of labour, inflation, PDRB, and interest rate to domestic investment (PMDN) in Central Java. The research benefit was to clarify factors that influenced domestic investment and gave insight and input for local government in formulating economy policy.One of method for analysing long-run and short run influence was by using dynamic model. In this research, model which applied was ENGLE GRANGER ERROR CORRECTION MODEL (EG-ECM) based on granger representation theoremResult of this research indicated that domestic investment one year ago was variable which influenced significantly in short run while rate of interest influenced in long run.